1986
DOI: 10.1021/bi00365a010
|View full text |Cite
|
Sign up to set email alerts
|

Leaving group dependence in the phosphorylation of Escherichia coli alkaline phosphatase by monophosphate esters

Abstract: Values of kcat and Km have been measured for the Escherichia coli alkaline phosphatase catalyzed hydrolysis of 18 aryl and 12 alkyl monophosphate esters at pH 8.00 and 25 degrees C. A Brønsted plot of log (kcat/Km) (M-1 s-1) vs. the pK of the leaving hydroxyl group exhibits two regression lines: log (kcat/Km) = -0.19 (+/- 0.02) pKArOH + 8.14 (+/- 0.15) log (kcat/Km) = -0.19 (+/- 0.01) pKROH + 5.89 (+/- 0.17) Alkyl phosphates with aryl or large lipophilic side chains are not correlated by the above equations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
3
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 35 publications
(32 reference statements)
2
70
3
1
Order By: Relevance
“…For each mutant, the kcat values for two different substrates are very similar, showing the same lack of dependence on the substrate leaving group that has been so thoroughly documented for the wild-type enzyme (4). For each enzyme, though, there is a marked increase in the Km value for phenyl phosphate relative to that for 4-nitrophenyl phosphate, in contrast to the reported (4) measurements for the wild-type enzyme. Based on the Michaelis-Menten parameters at pH 8 and 250C with two substrates of widely different pK values, a Bronsted plot of log (kcat/Km) vs. the pK of the leaving group would give a slope (PLG) of -0.36 for both mutants.…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…For each mutant, the kcat values for two different substrates are very similar, showing the same lack of dependence on the substrate leaving group that has been so thoroughly documented for the wild-type enzyme (4). For each enzyme, though, there is a marked increase in the Km value for phenyl phosphate relative to that for 4-nitrophenyl phosphate, in contrast to the reported (4) measurements for the wild-type enzyme. Based on the Michaelis-Menten parameters at pH 8 and 250C with two substrates of widely different pK values, a Bronsted plot of log (kcat/Km) vs. the pK of the leaving group would give a slope (PLG) of -0.36 for both mutants.…”
Section: Resultscontrasting
confidence: 84%
“…One of the striking features of alkaline phosphatase is the lack of sensitivity ofthe kcat/Km values for mnonophosphate ester hydrolysis toward the leaving group of the substrate. It has been proposed that the very small change in effective charge on the leaving group's oxygen in the course of the reaction is consistent with substantial electrophilic interaction of groups in the enzyme with this atom (4). The role ofthis electrophile could be filled by either a zinc ion or by the side chain of arginine-166.…”
mentioning
confidence: 98%
“…Adenosylmethionin-SynthetaseDie (S)-Adenosylmethionin-Synthetase (AMS) katalysiert die Bildung der Sulfonverbindung (S)-Adenosylmethionin (AdoMet), die als bedeutendes Methylierungsreagens in biologischen Systemen fungiert, aus L-Methionin und ATP (Abb 25…”
unclassified
“…The mechanism of transition state (TS) stabilization during enzymecatalyzed substrate hydrolysis of one member of this superfamily, Escherichia coli alkaline phosphatase (EcAP), has been subject of a large number of in-depth studies involving the experimental tools of linear free energy relationships (LFERs), kinetic isotope effects (KIEs), mutant studies, and structural analysis by X-ray crystallography. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] In addition computational simulations have been employed to pin-point transition state interactions. 26,27,[37][38][39][40][41] Sulfatase members of the AP superfamily have been studied less extensively.…”
Section: Introductionmentioning
confidence: 99%
“…of human arylsulfatase A, 48 choline sulfatase, 47 and the closely related phosphonate monoester hydrolase 49 ) have suggested that many of these conserved residues are indeed involved in the catalytic pathway in the enzyme active site. LFERs and KIEs have been measured for a number of phosphatases, [20][21][22][23]35,[50][51][52][53][54][55][56][57][58] but only one such study is available for sulfatases. 59 In addition to the family relationship, members of the AP superfamily are also typically catalytically promiscuous, [60][61][62] i.e.…”
Section: Introductionmentioning
confidence: 99%